Kajian Stockpile Management Terhadap Nilai Safety Stock Pada Stockpile 4 PT. Bukit Asam TBK, Tanjung Enim, Sumatera Selatan - Sarah Shania Ulfa Andisya; Tri Gamela Saldy (Journals Mining Engineering : Bina Tambang, 2021)
PT. Bukit Asam Tbk has a stockpile, one of which is in the OPB 4 area which is located in West Banko, Tanjung Enim, South Sumatra. stockpile data in May the percentage of load in in stockpile 4 has an achievement value of 77% and an achievement value of 83% load out in TLS 4. The final stock in the books on May 29, 2021 is 18,987.90 tons, but based on the measurement results of the final stock survey data is 793.85 tons. This thin stock affects the filling time of coal to trains in TLS 4 which can cause losses to the company if it experiences a long waiting time. Therefore, safety stock is needed as a safety stock if the stock is thin. Based on the results of research and analysis conducted at the research location which resulted in productivity and frequency of obstacles in the OPB 4 area, the productivity value of CHF 4 was 57.8% while in TLS 4 it was 54.9%. The average effective ultillize value for January 2021 - May 2021 is 56% for CHF 4 and 50% on TLS 4. The results obtained that the required safety stock value in the stockpile 4 area is 24,612,775 tons, with a stockpile management system that has a stockpile pattern at stockpile 4 is Chevron. Coal unloading system with FIFO (First In First Out) for the process of getting in and out of coal on the stockpile.